Psychometric properties of the Iranian version of self-care ability scale for the elderly - Mehrdad Amir-Behghadami; Jafar Sadegh Tabrizi; Mohammad Saadati; Masoumeh Gholizadeh (BMC Geriatrics, 2020)
Abstract Background Measuring self-care ability in elderly people needs specific instruments. The Self-care Ability Scale for Elderly (SASE) is one of the common instruments used for assessing self-care ability. The aim of this study was to assess the psychometric properties of the SASE among Iranian elderly population. Methods This cross-cultural adaptation study was carried out at Shahid Chamran and Shadpour Health Complex in Tabriz, Iran. The forward-backward procedure was applied to translate the SASE from English into Persian. Then, it was completed to 220 elderly people. A systematic random sampling method was used for sampling. Content validity was calculated through modified Kappa coefficient (modified CVI) based on clarity and relevance criteria. Reliability was measured by internal consistency and test-retest analysis. The construct validity also was assessed using Exploratory Factor Analysis (EFA). All the statistical analyses were performed using SPSS 21 statistical software package. Results The mean of self-care ability was 61.14 ± 21.08. The CVI and modified kappa were 0.91 and 0.92 for relevance and clarity, respectively. The Cronbach’s alpha coefficient was 0.73 and Intra-class correlation coefficient was 0.97. The results of EFA revealed a three-factor solution (‘ability to take care of personal responsibility’, ‘ability to take care for the goals’, and ‘ability to take care of the health’) that jointly explained for 64.61% of the total variance. Conclusion Results of the study showed that the Iranian version of the SASE has good psychometric properties and can be used in assessing the self-care ability of elderly people.